ANALISIS NORMATIF CASH WAQF LINKED SUKUK RITEL (CWLS RITEL) ATAU INVESTASI WAKAF UANG PADA SUKUK NEGARA - Hidayat, Umar Ade (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2023)
Waqf, as examined in various classical literature, has notably stringent conditions. Moreover, Cash Waqf Linked Sukuk Ritel (Cwls Ritel) or Investment in Cash Waqf Sukuk by the State is a relatively new form of waqf in the Islamic context. This has led to both support and opposition among contemporary scholars. The Indonesian Council of Ulama (Majelis Ulama Indonesia or MUI) addressed these perspectives through the National Sharia Council with number DSN-MUI/X/2019 on Wakaf Sukuk. However, the legitimacy of such waqf, based on normative Islamic studies guided by the Imams of the schools of thought, has not gained unanimous approval. The author draws personal conclusions based on the analysis of DSN MUI and the thoughts of the Imams. This research utilizes a literature review approach, characterized as descriptive-analytical and employing a normative framework. Classic works by the Imams and the Fatwa of DSN MUI on Wakaf Sukuk Ritel serve as the primary data sources. Data collection techniques involve observation and documentation, while data analysis utilizes data reduction, presentation, and drawing conclusions. According to the author's perspective, Cash Waqf Linked Sukuk Ritel (Cwls Ritel) or Investment in Cash Waqf Sukuk by the State is considered haram (forbidden) and should not be undertaken. This is because CWLS, as a waqf contract, should genuinely adhere to the waqf rules that have been in place since the time of the Prophet until now. CWLS itself involves two waqf contracts that seemingly contradict religious principles, namely waqf of money and temporal waqf.